The right to cyberbully? a gendered analysis during COVID-19 in Malaysia - Y. H. Loh, Benjamin; Vilashini Somiah; Nie, Kho Suet (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper explores the rhetoric of cyberbullying with a focus on Malaysian female influencers during the COVID-19 pandemic. The research objectives entailed identifying various critical rhetoric and attacks against female influencers on digital platforms, understanding diverse levels of cyberbullying experienced by influencers from different backgrounds, and analysing reasons behind online aggressive behaviours. The study's theoretical framework contributes to intersectionality theory by examining how the COVID-19 context shapes nuances in Female Cyber Victimisation. Methodologically, the research employs critical discourse analysis to study language in online comments and responses reflecting cyberbullying against Malaysian female influencers. The analysis covers social media platforms (YouTube, Instagram, Facebook, TikTok) and forums (Hardware Zone, Lowyat.net, Cari.com.my), focusing on cyberbullying content over two years. Three prominent Malaysian female influencers targeted by cyberbullying namely Cathryn Li, Veveonah and Ain Husniza were selected for their distinct demographics and contexts, showcasing varying cyberbullying rhetoric. Findings reveal male internet commenters' presumptions about female influencers are shaped by religion and modesty perceptions. Influencers challenging gender norms face escalated negativity. Cathryn Li, perceived as less modest and non-Muslim, faced extensive derogatory comments affecting her mental health. Ain Husniza faced mockery due to her Malay Muslim background, while Veveonah was targeted for political motives. Rooted in conservative gender roles, societal expectations contribute to targeting female influencers, resulting in ridicule and harassment. These cases underscore the intricate interplay of gender, cultural norms, and online harassment, highlighting the necessity for comprehensive interventions to combat cyberbullying and safeguard the well-being of female influencers.